AGAMA DAN FUNGSINYA DALAM KEHIDUPAN UMAT MANUSIA - Asir, Ahmad (Universitas Islam Madura, 2014)
Religion is an extremely important requirement for humans, whether consciously or not, every human being must need religion. man is a weak man. This is proven by the limited human mind. so that every man needs a mighty Essence everything to serve as a place to complain about any concerns. religion of Islam is the religion falsifies previous religions. sources of Islamic law are the Qur'an, al-hadith, and al ijtihad. In today's age of globalization, especially with the advancement of information technology, human morality is increasingly alarming. At times like this the human condition will leave the scholars as a place to pick science. This is because the things that become problems can be resolved with proper exit. But we need to realize is not always accessible material that is true and can be accounted for, because it did not rule makers sites are the ones who want to mislead Muslims.